The Expression Patterns of FAM83H and PANX2 Are Associated With Shorter Survival of Clear Cell Renal Cell Carcinoma Patients - Kim, Kyoung Min; Hussein, Usama Khamis; Bae, Jun Sang; Park, See-Hyoung; Kwon, Keun Sang; Ha, Sang Hoon; Park, Ho Sung; Lee, Ho; Chung, Myoung Ja; Moon, Woo Sung; Kang, Myoung Jae; Jang, Kyu Yun (Frontiers in Oncology, 2019)
FAM83H is primarily known for its role in amelogenesis; however, recent reports suggest FAM83H might be involved in tumorigenesis. Although the studies of FAM83H in kidney cancer are limited, a search of the public database shows a significant association between FAM83H and pannexin-2 (PANX2) in clear cell renal cell carcinomas (CCRCCs). Therefore, we evaluated the clinicopathological significance of the immunohistochemical expression of FAM83H and PANX2 in 199 CCRCC patients. The expression of FAM83H and PANX2 were significantly associated with each other. In univariate analysis, individual and co-expression pattern of FAM83H and PANX2 was significantly associated with shorter overall survival (OS) and relapse-free survival (RFS) of CCRCC patients: nuclear expression of FAM83H (OS; P < 0.001, RFS; P < 0.001), cytoplasmic expression of FAM83H (OS; P < 0.001, RFS; P < 0.001), nuclear expression of PANX2 (OS; P < 0.001, RFS; P < 0.001), cytoplasmic expression of PANX2 (OS; P < 0.001, RFS; P < 0.001), co-expression pattern of nuclear FAM83H and nuclear PANX2 (OS; P < 0.001, RFS; P < 0.001). In multivariate analysis, nuclear expression of FAM83H (OS; P < 0.001, RFS; P = 0.003) and the co-expression pattern of nuclear FAM83H and PANX2 (OS; P < 0.001, RFS; P < 0.001) were independent indicators of shorter survival of CCRCC patients. Cytoplasmic expression of FAM83H was associated with shorter RFS (P = 0.030) in multivariate analysis. In Caki-1 and Caki-2 CCRCC cells, knock-down of FAM83H decreased PANX2 expression and cell proliferation, and overexpression of FAM83H increased PANX2 expression and cell proliferation. These results suggest that FAM83H and PANX2 might be involved in the progression of CCRCC in a co-operative manner, and their expression might be used as novel prognostic indicators for CCRCC patients.